The impact on selection of non-alcoholic vs alcoholic drink availability: an online experiment - Anna K. M. Blackwell; Katie De-loyde; Gareth J. Hollands; Richard W. Morris; Laura A. Brocklebank; Olivia M. Maynard; Paul C. Fletcher; Theresa M. Marteau; Marcus R. Munafò (BMC, 2020)
Abstract Background Increasing the availability of healthier food increases its selection and consumption. However, there is an absence of evidence related to alcohol. This study aimed to estimate the impact of increasing the absolute and relative availability of non-alcoholic compared to alcoholic drinks on selection. We also assessed whether effects were modified by cognitive resource. Methods UK adult weekly alcohol consumers (n = 808) were recruited to an online experiment with a hypothetical drink selection task. Participants were randomly assigned to one of eight conditions, in a 4 (availability) × 2 (cognitive resource) factorial design. The four availability conditions were: i. Reference 1 (two non-alcoholic, two alcoholic drinks); ii. Reference 2 (four non-alcoholic, four alcoholic drinks); iii. Increased non-alcoholic drinks (six non-alcoholic, two alcoholic drinks); iv. Increased alcoholic drinks (two non-alcoholic, six alcoholic drinks). The two cognitive resource conditions were: a. Low (high time pressure); b. High (low time pressure). Logistic regression was used to assess selection of a non-alcoholic drink. Results 49% of participants selected a non-alcoholic drink in the Increased non-alcoholic drinks condition, compared to 36% in Reference 1, 39% in Reference 2, and 26% in the Increased alcoholic drinks condition. Non-alcoholic drink selection was similar between Reference 1 and 2 when the total number of drinks increased (absolute availability) but the proportion of non-alcoholic compared to alcoholic drinks (relative availability) was unchanged (OR = 1.15, 95% CI 0.77, 1.73). In contrast, the odds of selecting a non-alcoholic drink were 71% higher when both absolute and relative availability of non-alcoholic compared to alcoholic drinks was increased from Reference 1 to the Increased non-alcoholic drinks condition (OR: 1.71, 95% CI 1.15, 2.54), and 48% higher when increased from Reference 2 to the Increased non-alcoholic drinks condition (OR: 1.48, 95% CI 0.99, 2.19). There was no evidence of an effect of cognitive resource. Conclusions Greater availability of non-alcoholic drinks, compared to alcoholic drinks, increased their online selection, an effect that may be larger when changing their relative availability, i.e., increasing the proportion of non-alcoholic drinks. Naturalistic studies are needed to determine the impact of availability interventions on reducing alcohol purchasing and consumption.